Analysis of Students’ Difficulties in Understanding the Propagation (Da’wah) of Prophet Muhammad in Islamic Cultural History (SKI) at Islamic Primary Schools (MI) - Fany Hanum Salsabilla; Nurul Hidayatullah Hikmah; Lubna Hanna Barikliya; Haliza Ramadhani; Romzatul Isnaini; Naula Anvasa Tsabita; Siti Shofatul Ariffina; Dian Rif'iyati (The Future of Education Journal, 2026)
The learning of Islamic Cultural History (SKI) in Madrasah Ibtidaiyah (MI) often faces challenges, particularly students’ difficulties in understanding the preaching (dakwah) of Prophet Muhammad SAW, which contains exemplary values such as patience and honesty. These difficulties are caused by monotonous textual presentations, limited relevance to students’ daily lives, and students’ low literacy skills. This study aims to specifically analyze the difficulties experienced by MI students in understanding the material and to identify the contributing factors, including low learning motivation, limited instructional time, lack of visual media, and passive lecture-based teaching methods. The study employed a library research method by collecting data from reference books, national scientific articles, and relevant research reports obtained from academic databases. The data were analyzed qualitatively to formulate findings without plagiarism. The results reveal five main factors contributing to students’ difficulties: less contextualized material, low reading interest, limited instructional time, inadequate facilities, and low concentration caused by monotonous teaching methods. Therefore, interactive multimedia-based learning strategies are recommended to improve students’ understanding and internalization of the values of dakwah.